Fire Management Effects on Long‐Term Gopher Tortoise Population Dynamics. Issue 4 (18th March 2021) - Hunter, Elizabeth A.; Rostal, David C.
ABSTRACT: Long‐term datasets are required to understand the response of long‐lived organisms (e.g., gopher tortoises [ Gopherus polyphemus ]) to management actions, such as prescribed burns. Our objective was to estimate the effects of prescribed burning on gopher tortoise population dynamics over decadal time frames at Fort Stewart Army Reserve, southeastern Georgia, USA. We captured and marked adult tortoises from 1994–2020. In addition, since the early 1990s, managers at Fort Stewart collected spatial records of prescribed burns; thus, we could compare demography of the population to prescribed burning. We used a Bayesian hierarchical model (open population Jolly‐Seber model) to estimate population parameters (emigration and survival, immigration and recruitment, and adult abundance) and their relationships with years since burn. We observed opposing responses to years since burn at 2 sites: abundance and the probability of staying (survival plus not emigrating) increased within 1 site when it had been more recently burned (F zones), but abundance and probability of staying in a second site increased when it had been longer since the site was burned (E zones). Some of these effects were weak but indicative of different responses to burning between the sites. Although the sites experienced similar burning regimes, they differed substantially in other habitat features: the F zones had almost twice the tree cover and lower soil sand composition, indicating that tortoise population responses to burning depend on habitat context. We inferred that the primary mechanism for demographic responses to years since burn was likely emigrating adults, which indicates the need for more detailed movement data. Our results demonstrate that gopher tortoise population responses to prescribed burning are complex, context dependent, and primarily influenced by tortoise movements. Therefore, prescribed burn plans may best accommodate spatially dynamic tortoise populations when they create spatial heterogeneity in burn ages within the range of typical tortoise movements. © 2021 The Wildlife Society. Abstract : Gopher tortoises at 2 sites exhibited opposing population responses to prescribed burning, with differences likely attributable to habitat differences between the 2 sites. Tortoise populations likely responded to burning through increases or decreases in emigration; therefore, prescribed burn plans should be designed to accommodate spatially dynamic tortoise populations, allowing tortoises to select burn ages that are the most beneficial given other habitat conditions.